(untitled) (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2026)
Social media has become a signifcant part of global society, serving not only as a communication tool but also as a platform for dissemination knowledge and entertainment. One of the most widely used platforms today is TikTok, which allows trends to spread rapidly through short-form video content. One viral trend featured a certain part from the Japanese idol song Ai♡Scream! with its popular tagline “Ruby-chan? Hai! Nani ga suki?”by the limited-time unit AiScReam. The song embodies elements of Japanese culture, particulary idol culture and kawaii aesthetics. However, as the trend spread globally, a process of recontextualization and cultural transformation occurred. This study aims to analyze how the original meaning of the content shifted, using Barthes’ semiotic theory. The data consists of five purposively selected TikTok videos accompanied by public comments. The results reveal that the original meanings—centered around cuteness and idol-style intimacy—were transformed into forms of parody, memes, and humor within global digital culture.